2008
DOI: 10.1111/j.1349-7006.2007.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus associated gastric carcinoma: Epidemiological and clinicopathological features

Abstract: In this paper, the roles of Epstein-Barr virus (EBV) in gastric carcinogenesis are discussed, reviewing mainly epidemiological and clinicopathological studies. About 10% of gastric carcinomas harbor clonal EBV. LMP1, an important EBV oncoprotein, is only rarely expressed in EBV-associated gastric carcinoma (EBV-GC) while EBV-encoded small RNA is expressed in almost every EBV-GC cell, suggesting its importance for developing and maintaining this carcinoma. In addition, the hypermethylation-driven suppressor gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 38 publications
5
112
3
3
Order By: Relevance
“…To date; there has been no study from Brunei Darussalam looking at EBV and gastric cancer. Our study showed that the estimated point prevalence of EBVaGC was 30.9%%, much higher than rates reported from other countries, generally around 10% of all gastric cancer (Lopes et al, 2004;Zur et al, 2004;Akiba et al, 2008).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…To date; there has been no study from Brunei Darussalam looking at EBV and gastric cancer. Our study showed that the estimated point prevalence of EBVaGC was 30.9%%, much higher than rates reported from other countries, generally around 10% of all gastric cancer (Lopes et al, 2004;Zur et al, 2004;Akiba et al, 2008).…”
Section: Discussioncontrasting
confidence: 61%
“…Shibata and Weiss, in 1992 later reported that EBV involvement can also been extended to a subset of ordinary gastric carcinoma (Toshikazu et al, 1998). Studies have estimated 10% of gastric cancer to be positive, and hence associated with EBV (Lopes et al, 2004;Zur et al, 2004;Akiba et al, 2008). These findings imply that EBV may play a role in the development of EBV positive gastric cancer or EBV associated gastric cancer (EBVaGC).…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of EBV infection on GC development and treatment is still unclear. EBV-positive GC presents histologically and pathologically different features from EBV-negative GC (Akiba et al, 2008;Lee et al, 2004). EBV-positive GC exerts modulated latency 1, expressing latent genes such as EBNA1, LMP2A, BamHI-A rightward frame 1 (BARF1), and EBV-encoded RNAs (EBERs) (Imai et al, 1994;Oh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies indicated that lifestyle or occupational factors may exist among males [10,23,24].The highest incidence of EBV in Gastric cancer was at (50-59) year age [21,25]. Occurrence in elderly persons and male predominance are common in EBV-associated gastric carcinomas [26].…”
Section: Discussionmentioning
confidence: 99%